The history behind ALS type 8: from the first phenotype description to the discovery of VAPB mutation - NOVIS, Luiz Eduardo; SPITZ, Mariana; TEIVE, Hélio A. G. (Arquivos de Neuro-Psiquiatria, 2021)
Over the past 68 years, the Finkel type late-onset adult autosomal dominant spinal muscular atrophy (SMA) that is allelic with amyotrophic lateral sclerosis-8 (ALS8) gained a genotype-phenotype correlation among the motor neuron diseases through the work of groups led by Zatz and Marques Jr.
Keywords: Spinal muscular atrophy; amyotrophic lateral sclerosis; ALS8; VAPB gene